Identification of novel target genes in exaggerated cardiac remodeling following myocardial infarction in diabetes - Duan, Yanru; Zhang, Shihan; Xia, Yihua; Li, Huili; Liu, Demin; Du, Yunhui (Frontiers in Endocrinology, 2025)
IntroductionDiabetes mellitus is a major risk factor for myocardial infarction (MI), yet its molecular mechanisms exacerbating post-MI cardiac remodeling remain unclear.MethodsType 2 diabetes mellitus mouse model was developed through a high-sugar and high-fat diet (HFD), followed by MI surgery. Four weeks post-surgery, cardiac function was evaluated via echocardiography, and cardiac pathology was examined using Masson's trichrome and wheat germ agglutinin staining. High-throughput sequencing identified differentially expressed mRNAs and long non-coding RNAs (LncRNAs) in diabetic mice with MI. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, along with LncRNA-target-gene analysis, were performed. Validation in human samples of diabetic patients with STEMI confirmed the influence of HFD on the expression of specific genes.ResultsThe results demonstrate that diabetes significantly impairs cardiac function, exacerbates cardiac fibrosis and hypertrophy. In addition, our extensive examination of human samples has conclusively demonstrated that diabetes significantly modulates the expression of genes (Rapgef5 and Ing1) within the cardiac tissue of individuals afflicted with STEMI, underscoring the intricate interplay between these conditions. In addition, we have found that Rapgef5 and Ing1 are involved in diabetes-mediated cardiomyocyte apoptosis and proliferation following myocardial infarction.DiscussionDiabetes aggravates post-MI remodeling via Rapgef5/Ing1-mediated apoptosis and proliferation, these findings highlight novel therapeutic targets for diabetic cardiovascular complications.